MULCH STRATEGIES FOR WEED MANAGEMENT IN PEPPERMINT (MENTHA PIPERITA) CULTIVATION - Dragumilo, Ana; Marković, Tatjana; Prijić, Željana; Đurović-Pejčev, Rada; Radanović, Dragoja; Božić, Dragana (Acta herbologica, 2024)
Basic characteristics of different mulching materials and the most important characteristics (number and biomass) of weed that managed to penetrate the mulch barriers are presented in this paper. The study examined 9 organic mulches (straw, pine bark, acacia sawdust, cardboard, dry pine needles, shredded corn stalks, acacia bark, plant composts 1 and 2), 1 biodegradable mulch (black mulch film), and 4 plastic mulch films (silver-black, perforated black, black, black "agrotextile") tested on peppermint (Mentha x piperita) in Serbia. The most numerous recorded weeds were Agropyron repens, Avena fatua, Picris hieracioides, Setaria viridis, and Rumex crispus. The number and biomass of all weed species were measured once per season, before the first harvest of peppermint. Compared to the control treatment, 12 out of 14 applied mulches used for weed control showed positive effects on peppermint. The mulches affected the occurrence (reduction from 9.7% to 100%) and biomass of weeds (reduction from 30% to 100%). Four mulches were assessed as good solutions for weed control in peppermint, namely two organic: acacia sawdust and dry pine needles, and two films: silver-brown and black "agrotextile".
Keywords: weed, mulch film, mulching, weed's number, weed's biomass